Catalogue of the moniligastrid earthworms (Clitellata, Moniligastrida, Moniligastridae) of the world - Narayanan, S. Prasanth; Paliwal, R.; Thomas, A.p.; Julka, J.m. (Zootaxa, 2024)
This study presents a comprehensive catalogue of the moniligastrid earthworms (Moniligastrida, Moniligastridae) of the world. A total of 176 valid species/subspecies belonging to 5 genera are known to exist in this primitive family. Drawida is the speciose genus with 147 species/subspecies. Of the various moniligastrids, three species of Drawida are considered as peregrine outside its normal Asian range. Among the valid species, occurrence of 30.68% are known only from the type locality. It is noteworthy that the types of 125 (71.02%) species are currently known to exist in various repositories around the world. The existence of the remaining species can only be inferred from the literature since their types are either non-existent, missing, dried out, or lost. Present catalogue includes valid scientific names, synonyms, type locality, type respository details along with registration number, geographic distribution pattern within its native range, and references.